Business Valuation: A Start-Up Online Company (The Indonesian Journal of Business Administration, 2012)
The positive trend of Internet or online industry in Indonesia has continued steadily. The prove is that the big companies, such as Telkom through Plasa.com and Djarum Group through Blibli.com, have begun to enter this promising industry. In addition, more and more new online start-up companies were established and also the number of members in start-up communities shows a significant growth. Furthermore, believing in the promising future of this business, more private investors and venture capitals, such as InvestIdea, Batavia Incubator, Merah Putih, Project Eden, etc, are interested in investing in high potential new start-up online companies. Every investor needs to know how to value the company. This problem is faced not only by the investors, but also the owners of the start-up company. Despite the potential growth of the business, in most of the cases, a start-up company has no financial history, negative earning, and sometimes no industry comparison. And it is even more complicated in Indonesia since the industry is relatively new. Therefore, it is difficult to find the related data and information to be analyzed. Some alternative methods available to do valuations are using the Discounted Cash Flow to determine the intrinsic value of a company, the relative valuation method (using P/E Ratio or other ratios), and net asset value. However, this paper will focus on the Discounted Cash Flow method because it shows the projection of the generated cash flow objectively and calculate the fair or intrinsic value of the company, and this method still can be used in situations where the company has negative earnings and equity. Bistip.com is taken as the case study in this paper. Keywords: business valuation, start-up online company, discounted cash flow